The Role and Importance of the Cluster Approach in the Development of Domestic Tourism of the Russian Federation - LARIONOVA, Anna A.; DZHANDZHUGAZOVA, Elena A.; CHERNIKOVA, Ludmila I.; CHUDNOVSKIY, Alexey D.; FAIZOVA, Guzel R. (Journal of Environmental Management and Tourism, 2017)
The relevance of the topic is determined by the fact that tourist's cluster plays an important role in the development of not only municipalities, regions of the Russian Federation, federal districts, but the country as a whole, solving social problems, including those that relate to the creation of jobs, the problems of improvement in the quality of domestic tourist's products and services and incensement in investment and tourist's potential of the regions and the country. The aim of the study of the role of clusters in the development of domestic tourism was a compilation of existing research approaches and results of original research in this field. The leading methods to solve this problem are the methods of systemic, economic and statistical analysis, quantitative and qualitative research. In support of the main provisions of the authors also relied on expert methods of obtaining and processing information. The article gives the basic theoretical and practical interpretation of the definition of tourist's cluster. The mechanisms and identified issues of state participation in the formation and development of the tourist cluster, based on the research methodology and practices, as well as authoring, compiled tools of state support for domestic tourism development. Article Submissions are of practical value to planners in the tourism sector, tourism administrations, marketing professionals of tourism enterprises.